Population Dynamics of Pseudomonad fluorescent Isolate Pf-122 In Formula in Different Save Containers - Wuryandari, Yenny; Wiyatiningsih, Sri; Suwandi (Nusantara Science and Technology Proceedings, 2020)
The development of biopesticide formulas is carried out by optimizing the use of natural media materials. The formula is made easily, cheaply, and can still maintain the viability of bacteria. This study aims to determine the effect of various formulas and storage containers on the viability of Pseudomonad fluorescent Pf-122. Eight kinds of formulas include; 1) Non-hydrolyzed rice crab at a dose of 400 (K400), 2) at a dose of 200 (K200), 3) Hydrolyzed papaya rice crab at a dose of 400 (KP400), 4) at a dose of 200 (KP200), 5) Pineapple hydrolyzed rice crab with a dose of 400 (KN400), 6). at a dose of 200 (KN200), 7) Media King'S B at a dose of 400 (KB400), 8). at a dose of 200 (KB200). The formula is stored in a plastic and paper storage container. Population dynamics were observed at 1-week intervals. In the paper container, at week 1, the highest bacterial population was in the KP 400 and K400 formulas. At weeks 3 to 8, the population experienced a very rapid decline in all formulas, except for the KN400 formula. In the KN400 formula, at weeks 2 and 3, the population reached 107 CFU / ml and experienced a slow decrease until week 8 (population 101CFU / ml). In plastic containers, at week 1, the highest bacterial population was in the formula KB200, K200, and KP400. At the 3rd to 8th week of observation, the population experienced a rapid decline in all formulas, except for formula K400. In the K400 formula, starting from weeks 2 and 3, the population reached 106 CFU / ml and decreased until the 8th week (population 103CFU / ml). As for the KN400 formula, it can still last until the 7th week with a population of 102 CFU / ml. The longest survival rate of Pf-122 bacteria in the two storage containers was the KN400 formula. The best survival time of Pf-122 bacteria (long-lasting time and high population) is the formula of rice crab with a dose of 400 (K400) in a plastic container.